Packed-Bed Photocatalytic Reactors. A Packing Structure Model and Its Experimental Validation with Computerized Tomography - Irazoqui, Horacio Antonio (2004)
A statistical model is proposed for the description of the spatial structure of a packed bed of spherical-like particles in terms of one- and two-bead distribution functions. This is the first step toward the full modeling of the radiation field in an annular photocatalytic reactor, mainly where the interaction between radiation and the packed beads is concerned. The model has been validated against tomography experiments performed on an up-scaled packing prototype. The three-dimensional structure of its loose random packing has been digitized. On the basis of this structural information, the experimental version of the one-bead distribution function, as well as those of the conditional distribution and the solid volume fraction, could be constructed without mediating models. Then the parameters of the proposed statistical model could be determined by nonlinear regression. The agreement between the functions constructed experimentally and their model-predicted counterparts with the set of regressed model parameters is remarkable considering the highly structured shapes of their profiles. Exact relationships have been established to scale those model parameters bearing dimensions to packings with different bead radii.